Geomorphological Assessment to Tract the Flow Evolution of Kali Putih, Srumbung District, Magelang Regency, Central Java, Indonesia - Sari Bahagiarti Kusumayudha; I Made Oki Sanjaya; Helmy Murwanto; Sugeng Raharjo (UIR PRESS, 2020)
Kali Putih (The White River) is located in Srumbung district, Magelang regency, Central Java, Indonesia. It is originated from the upper slope of Merapi volcano, flowing to the Southwest direction. Kali Putih belongs to one of the most channels where frequently flowed by lahar of Merapi volcano. Based on geomorphological and geological traces found at the surrounding of modern Kali Putih channel, this indicated that the flow of Kali Putih has undergone displacement several times. The position of ancient river valley in the past has changed into the modern river valley in the present time. The existence of ancient Kali Putih is exhibited by the presence of large dry valley morphology associated with volcanic blocks, gravels, and sand sized materials with various sorting, representing the characteristics of lahar and alluvial deposits. In the present time, the former river channels are currently used by local people for agricultural and fisheries land.